Progressive and Traditional Orientations to Prosecution: An Empirical Assessment in Four Prosecutorial Offices - Meldrum, Ryan Charles (Criminal justice and behavior, 2021)
In recent years, accounts of the so-called progressive prosecutor have been juxtaposed against the more traditional, law-and-order prosecutor in the United States. Yet, little effort has been made to empirically investigate these orientations among prosecutors. In this multijurisdictional study, prosecutors were asked to rate the importance of a variety of prosecutorial priorities. A factor analysis of these ratings indicates the existence of two distinct orientations toward prosecution. The first reflects a progressive orientation emphasizing social justice priorities, and the second reflects a traditional orientation emphasizing priorities pertaining to formal aspects of case processing. Results also indicate that scoring higher on the progressive orientation is associated with holding less punitive attitudes toward criminal defendants, whereas scoring higher on the traditional orientation is associated with holding more punitive attitudes. Discussion centers on the implications of the findings for recent calls regarding the reform of the criminal justice system.